Perception of Medical Students towards Cadaveric Dissection at a Medical College,Pokhara - Yadav, Bijendra Prasad; Baral, Prakash; Shrestha, Ripti (Nepal Journal of Health Sciences, 2025)
Introduction: Cadaveric dissection remains the gold standard for teaching gross anatomy, yet student perceptions vary, particularly regarding its educational value, emotional impact, and the role of alternative modalities. Objective: To assess medical student’s perceptions of cadaveric dissection in the anatomy dissection hall at a medical college in Pokhara, Nepal. Methods: A descriptive cross-sectional study was conducted among all first year MBBS and BDS students (n=130). A validated, pretested 32 item questionnaire covered five domains: educational value, negative experiences/formalin burden, emotions/coping, ethics/professional attitudes, and preferences for alternatives. Descriptive statistics, chi square test and logistic regression were used to analyse data. Results: Of 130 students, 117 participated (response rate 90%). Most agreed that dissection deepened understanding (88.9%), improved retention (86.3%), and provided essential 3-D orientation (83.8%). Negative experiences included dislike of formalin odor (78.6%) and perceived time burden (69.2%). Initial anxiety was reported by 42.7%, with 71.8% noting anxiety reduction after repeated exposure. Respect for cadaver personhood was nearly universal (95.7%). Prior exposure to the deceased significantly reduced high initial anxiety (OR=0.46, p=0.035). Conclusion: First year students strongly valued cadaveric dissection, preferred it over sole virtual methods, and supported blended resources. Enhancing ventilation, early coping support, and humanistic framing can optimize learning.